A study to know the level of awareness of health care workers towards microbial occupational exposure and the impact of training some Jizan province hospitals - Alharbi, Mohammed Ghallab; Balkhyor, Mansour Ahmed; Madkoor, Mohammed Hussain (Journal of Risk and Crisis Management, 2020)
This research aims to identify the level of awareness (knowledge, behavior and practices) of workers in the field of health care towards the occupational hazards surrounding them in hospitals in the Jazan region in the Kingdom of Saudi Arabia, a study to measure awareness of the use of (KAP), and also aims to know the impact of training at the level of awareness. The descriptive analytical survey method and the quazi experimental approach were used through the pre and post exam for its suitability for this research. The study was conducted on a sample size of 326 participants’categories are (doctors, nursing, and laboratory specialists) and the experimental group to conduct the training was on Damad and Al-Umais Hospitals The results of the study showed that the level of knowledge was good before the training program and the axes of attitude, practices and training were not satisfactory in the total group before the program. After the training program, the levels of all axes increased with arithmetic averages, some of which reached 100%, which confirms the need to intensify training programs for workers and this is what The researcher recommended it in addition to the need to have a department responsible for monitoring and developing measures to protect against occupational exposures and raise awareness among workers.